VACCINE IMMUNIZATION FOR PREVENTION OF PNEUMOCOCCAL, HAEMOPHILUS INFLUENZAE AND FLU AMONG SICKLY CHILDREN, WHO OFTEN SUFFER FROM PERSISTENT HETEROSPECIFIC INFECTIOUS PATHOLOGY OF THE BRONCHOPULMONARY SYSTEM - L.I. Ilienko; M.P. Kostinov; M.V. Garashchenko; O.V. Kyt'ko; N.V. Ovechkina; T.G. Kats ("Paediatrician" Publishers LLC, 2006)
Among serious diseases of the lower respiratory tract a special place is taken by pneumonias and chronic infectious respiratory diseases caused by pneumococcus and Haemophilus influenzae type b (HIB). The research purpose is to determine the effectiveness of vaccine combined application to treat sickly children, who often suffer from persistent infectious pathology of the respiratory tract, for flu, pneumococcal and HIB disease. 110 children aged between 3 and 12 have been vaccinated. The first part of research implied children vaccination by means of Actahib and Pneumo 23 vaccines (Sanofi Pasteur, France), the second one consisted in immunization of children with the same pathology by means of Pneumo 23, Actahib and Vaxigrip vaccines (Sanofi Pasteur, France). The researches established that within a year after HIB and Pneumo 23 vaccination the frequency of upper and lower respiratory tract acerbations reduced by 2,3 times on average; likewise, the number of system antimicrobial dosage reduced by 7,4 times along with the total duration of dosage; the carrier state of S. pneumoniae reduced by 3,7 times, H. influenzae - by 3,9 times. In the course of application of three vaccines, the frequency of persistent heat erospecific infectious bronchopulmonary pathology acerbations reduced by 3,3 times. The carrier state of S. pneumoniae reduced by 2,5 times, H. influenzae - by 4,1 times. Thus, vaccine immunization to treat for flu, pneumococcal and HIB disease in various combinations may be recoma mended for wider application to reduce the frequency and severity of heat erospecific infectious respiratory diseases among sickly children, who often suffer from various illnesses. Key words: children with recurrent diseases, vaccination, prevention, flu, H. Influenzae, S. pneumoniae.